Clinical safety and efficacy of thrombolytic therapy with low-dose prolonged infusion of tissue type plasminogen activator in patients with intermediate-high risk pulmonary embolism. Issue 8 (December 2020) - Güner, Ahmet; Kalçik, Macit; Aykan, Ahmet Ç.; Gürsoy, Mustafa O.; Kalkan, Ali K.; Astarcioğlu, Mehmet A.; Ertürk, Mehmet; Uzun, Fatih; Güner, Ezgi G.; Yildiz, Mustafa; Özkan, Mehmet
Abstract : N/A: The patients with intermediate-high risk pulmonary embolism who have acute right ventricular (RV) dysfunction and myocardial injury without overt hemodynamic compromise may be candidates for thrombolytic therapy. Alternative low-dose thrombolytic therapy strategies with prolonged infusion may further decrease the complication rates as its efficacy and safety have been previously proven in the management of prosthetic valve thrombosis. In this study, we aimed to investigate the clinical outcomes of low-dose prolonged thrombolytic therapy regimen in intermediate-high risk pulmonary embolism patients. This study enrolled 16 retrospectively evaluated patients (female 9, mean age: 70.9 ± 13.5 years) with the diagnosis of acute pulmonary embolism who were treated with low-dose and slow-infusion of tissue-type plasminogen activator (t-PA). All patients underwent transthoracic echocardiography and computed tomography scan for assessment of thrombolytic therapy success. Low-dose prolonged thrombolytic therapy was successful in all patients. The mean t-PA dose used was 48.4 ± 6.3 mg. There was residual segmental thrombus in nine (56.3%) patients after thrombolytic therapy. The arterial oxygen saturation and tricuspid annular plane systolic excursion increased after thrombolytic therapy whereas heart rate, RV to left ventricular (LV) ratio, systolic pulmonary artery pressure, and the frequencies of hypotension and tachypnea significantly decreased. There was no cerebrovascular accident or major bleeding requiring transfusion. There were two minor bleedings (12.5%) including hemoptysis and epistaxis. Thrombolytic therapy in these intermediate-high risk pulmonary embolism patients was associated with excellent clinical outcomes and survival to discharge (100%) without any 60-day mortality. Prolonged thrombolytic therapy regimen with low-dose and slow-infusion of t-PA may be associated with lower complication rates without comprimising effectiveness in patients with acute intermediate-high risk pulmonary embolism.